Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15

Comparative catalytic activity of Mn(Salen) complexes grafted on SBA-15 functionalized with amine, thiol and sulfonic acid groups for selective aerial oxidation of limonene - Salkia, Lakshi; Srinivas, Darbha; Ratnasamy, Paul (Microporous and Mesoporous Materials, 2007)
SBA-15 molecular sieves were functionalized with propylamine, propylthiol and propylsulfonic acid groups. Mn(Salen)Cl complexes were grafted on these organo-functionalized SBA-15. The support and the type of organo-functional group influenced the electronic structure (oxidation state and redox behavior) and chemo selectivity of the Mn-complexes in the oxidation of limonene. The Mn ions were reduced from +3 to +2, the extent of this reduction on different supports decreasing in the order: SBA- 15-pr-SH > SBA- 15-prSO(3)H > SBA-15-pr-NH2- Mn(Salen)Cl supported on propylthiol-functionalized SBA-15 yielded the 1,2-limonene epoxide with 100% chemo- and regioselectivity. Higher electron density at the site of Mn ions and the consequent lower redox potential of the Mn-complexes on immobilization are the probable causes for their efficient and selective catalytic activity. Solvents, additives (N-MeIm) and co-reagents (iso-butyraldehyde), which facilitated formation of Mn2+ ions, enhance the catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction and the extent of this with different catalysts decreased in the order: SBA-l5-pr-NH2-Mn(Salen)Cl > SBA- 15-pr-SO3H-Mn(Salen)Cl > SBA- 15-pr-SH-Mn(Salen)Cl. (C) 2007 Elsevier Inc. All rights reserved

Estimation of free fatty acid content in oils, fats, and biodiesel by (1)H NMR spectroscopy - Satyarthi, Jitendra K.; Srinivas, D.; Ratnasamy, Paul (Energy & Fuels, 2009)
A novel (1)H NMR method for the quantification of free fatty acid (FFA) content in vegetable oils, animal fats, and biodiesel is reported. Nonedible oils and animal fats, which are increasingly being explored as cheaper, renewable feed stocks for biodiesel production by transesterification with methanol, contain a significant amount of FFA along with other acidic impurities. The (1)H NMR spectroscopic method is found to be more accurate than the conventional titrimetric analysis for the estimation of FFA content especially in those cases where acidic entities other than the FFA are also present in the feedstock. The titrimetric methods provide a gross acid value which corresponds to that of FFA and other acidic impurities. Our NMR method provides the FFA content exclusively. In the case of refined edible oils (wherein the other acidic impurities are negligible), the results obtained from the (1)H NMR method are comparable with those from the titrimetic analysis.

Selective oxidations over zeolite- and mesoporous silica-based catalysts: selected examples - Ratnasamy, Paul; Srinivas, Darbha (Catalysis Today, 2009)
Selective oxidation of hydrocarbons/terpenes in the liquid phase are reported over three categories of zeolite- and mesoporous silica-based catalysts: (1) transition metal complexes (metal phthalocyanines, copper acetate dimers and Co/Mn acetate trimer) encapsulated in zeolite-Y, (2) transition metal complexes (Mn-Salen), grafted on SBA-15, and (3) transition metal ions in framework positions of zeolites and mesoporous molecular sieves like Ti-silicates. Upon heterogenization, the metal complexes exhibited enhanced catalytic acitivity/selectivity. The causes for the enhanced catalytic activity/product selectivity have been explored. Dimer formation (copper acetate) or geometric distortion in the zeolite cavities (metal phthalocyanines) and consequent changes in energy levels and redox potentials are shown to modify the catalytic activity (in the selective oxidation of hydrocarbons) of the encapsulated metal complexes. In the case of Mn-Salen grafted on SBA-15, increasing the acidity of the siliceous surface (by -SO(3)H groups, for example) leads to a more facile reduction of the Mn ions and, thereby, enhanced catalytic activity in the selective epoxidation of limonene. When Ti ions are introduced in framework positions, reactive metal-oxo species are formed on contact with H(2)O(2) or O(2), Which influence the mode of O-O cleavage (heterolytic/homolytic) and product selectivity. The structure-function relationships in these catalysts are reported. (c) 2008 Elsevier B.V. All rights reserved.
18th National Symposium and Indo-US Seminar on Catalysis, Indian Inst Petroleum, Dehradun, INDIA, APR 16-18, 2007
Keywords: Mn-Salen; Oxidation of hydrocarbons and limonene; Reactive oxo species; Selective oxidation; Titanosilicates; Zeolite-encapsulated metal complexes

Synthesis of framework Ti-substituted, 3-D hexagonal, mesoporous Ti-SBA-12 for selective catalytic oxidation - Kumar, Anuj; Srinivas, Darbha; Ratnasamy, Paul (Chemical Communications, 2009)
Framework Ti-substituted, 3-D hexagonal mesoporous, Ti-SBA-12, obtained for the first time by direct hydrothermal synthesis, oxidises bulky molecules such as cyclohexene and cyclooctene to the epoxides with >96% selectivity at high conversion levels (>60%).

Influence of surface hydrophobicity on the esterification of fatty acids over solid catalysts - Satyarthi, Jitendra K.; Srinivas, Darbha; Ratnasamy, Paul (Energy & Fuels, 2010)
The relative roles of surface acidity and hydrophobicity in the methylation of fatty acids (C(8) - C(18)) to the corresponding methyl esters were investigated over three solid acid catalysts: Fe-Zn double-metal cyanide (DMC), sulfated zirconia (SZ), and Al-MCM-41. The esterification reaction was faster and the apparent activation energy was lower over SZ and Al-MCM-41 than on DMC because of their higher acid strength, specific surface area, and pore diameter. Over SZ and Al-MCM-41, the apparent activation energy for esterification increased with the chain length of the fatty acid. A reverse trend, however, was observed over DMC. The relative adsorption of methanol and fatty acids (compared to water) was higher on DMC than on SZ and Al-MCM-41. Hence, in addition to the acidic and textural properties, surface hydrophobicity and relative surface coverage by reactants/products also play an important role in reactions of long-chain fatty acids with alcohols on solid catalysts.

Catalytic activity of ZIF-8 in the synthesis of styrene carbonate from CO2 and styrene oxide - Zhu, Minqi; Srinivas, Darbha; Bhogeswararao, Seemala; Ratnasamy, Paul; Carreon, Moises A. (Catalysis Communications, 2013)
The catalytic activity of ZIF-8 in the synthesis of styrene carbonate from carbon dioxide and styrene oxide is presented. ZIF-8 crystals displayed catalytic activity even at temperatures as low as 50 degrees C, with styrene carbonate yields as high as similar to 54% at 100 degrees C. In contrast to many prior-art catalysts, solvents or co-catalysts were not required. Pyridine and ammonia were used as probe molecules to estimate the type and density of acid sites in fresh and reused ZIF-8 catalysts. DRIFT spectroscopy of adsorbed pyridine revealed the presence of both Bronsted (B) and Lewis (L) acid sites. The B-sites have nearly vanished in the case of recycled ZIF-8 catalysts. The simultaneous presence of both the acid sites and the nitrogen basic moieties from the imidazole linker in ZIF-8 promoted the adsorption of the CO2 on the solid surface and its further conversion to the cyclic carbonate. The ZIF-8 catalysts could be recycled and reused without significant loss in catalytic activity. Published by Elsevier B.V.
Keywords: CO2 conversion; cyclic carbonates; Styrene carbonate; Zeolitic imidazolate frameworks; ZIF-8